(untitled) (World Bulletin of Management and Law, 2024)
This article explores the theoretical underpinnings of methodological preparedness among future foreign language teachers. It examines the key concepts, components, and historical development of methodological preparedness and its relevance in contemporary foreign language education. The study identifies core competencies required for effective teaching and highlights influential theories and models that inform best practices in developing methodological readiness